Discourses about 'foreigners' in contemporary Austria - Aigner, Petra Irene (Trinity College (Dublin, Ireland). Department of Sociology, 2005)
A number of events, such as the fall of the Iron Curtain in 1989, the opening up of Eastern Europe, the Yugoslavian crisis in the 1990s and the Austrian membership of the European Union since 1995 have contributed to an increase in the numbers of immigrants entering Austria. These events have led to an upsurge in debates about immigration and immigrants in contemporary Austria at national macro as well as regional microstructures of society, including the political elites as well as the regional actors of the everyday. Differing discourses range from exclusionary expressions and the rejection of foreigners, to welcoming articulations such as the appreciation of cultural diversity.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin